Model Pengembangan Profesionalisme Guru - Rafiq, Abdul; Suyatno; Santosa, Achadi Budi; Hidayati, Dian (Academy of Education Journal, 2024)
The aim of this study is to investigate the professional development model of teachers implemented at SD Al-Imam Islamic School in Balikpapan. Expertise of the teacher becomes a crucial factor in raising student achievement in education as curricula and educational technologies advance. Observation, interview, and document review are used as qualitative methods together with case study research to gather data. According to the study's findings, this school employs a variety of professional development models, including career-growth models based on skill, knowledge, collaboration, innovation, and performance evaluation. This approach is not limited to enhancing technological proficiency; it also promotes the development of Islamic character. Thus, the development of the teacher's professionalism at SD Al-Imam Islamic School Balikpapan has a significant impact on student learning outcomes and serves as a model for other schools seeking to create a comprehensive and holistic learning environment.